Multicomponent sorption of hexane isomers in zeolite BETA - Bárcia, Patrick da Silva (2007)
Breakthrough curves of single, binary, ternary, and quaternary mixtures of hexane (C-6) isomers n-hexane (nHEX), 3-methylpentane (3MP), 2,3-dimethylbutane (23DMB), and 2,2-dimethylbutane (22DMB) were performed in commercial pellets of zeolite BETA (BEA structure), covering the temperature range between 423 and 523 K and partial pressures up to 30 kPa. From these data, single and multicomponent adsorption equilibrium isotherms were collected. A tri-site Langmuir model (TSL) was developed to interpret the equilibrium data based on considerations about zeolite structure, and a dynamic adsorption model was tested predicting with a good accuracy the behavior of multicomponent fixed-bed experiments. At the partial pressures studied, the sorption hierarchy in the zeolite BETA is nHEX >>> 3MP > 23DMB >> 22DMB. BEA structure demonstrates a significant selectivity between C-6 isomers, especially at low coverage, giving a good perspective regarding their separation by adsorption processes. (c) 2007 American Institute of Chemical Engineers.